The glocalization of antimicrobial stewardship - Olivier Rubin (BMC, 2019)
Abstract This brief commentary argues that glocal governance introduces a fruitful new perspective to the global governance debate of AMR, and cautions against too strict a focus on establishing globally binding governance regimes for curbing AMR.